PELATIHAN INTEGRASI TEKNOLOGI BERMAKNA DALAMPROSES PEMBELAJARAN UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Sadikin, Irma Savitri; Nurchaerani, Meiyanti; Lutfiyah, Lutfiyah (Community Services and Social Work Bulletin, 2022)
The present education policy of the Indonesian government has implemented post-Covid-19 face-to-face (offline) learning at nearly all levels of education, excluding primary school. This encouraged teachers to adjust teaching and learning to boost engagement in class. Educators must be able to facilitate engaging, dynamic, and fruitful learning by integrating meaningful learning technology models in to classroom. The purpose of this paper is to portray elementary school teachers' implementation of programs that promote competence of relevant offline learning. Guidance offered by the Community Service Lecturer Team (PKM) during three sessions: introduction, application, and practice. As a result of this commitment, subject teachers at SDIT have access to a variety of interactive, relevant, and enjoyable learning experiences through the use of authentic sources obtained from websites and applications that can be utilized in the classroom, therefore, allow learners to acquire the learning competencies.